THE EFFECT OF VIRTUAL DRY LAB ON NURSING STUDENTS’ COMPLIANCE OF USING HANDOVER WITH SBAR METHOD - Wiwin Nur Aeni; Muhammad Saefulloh; Bestina Nindy Virgiani; Ryan Hara Permana (Asosiasi Institusi Pendidikan Ners Indonesia (AIPNI), 2023)
Introduction: The nursing education curriculum requires students to achieve effective communication competence, including handover using the SBAR method. High-fidelity learning media is needed that is able to internalize the experience of activities as in their realization. Learning media with Virtual Dry Lab (VDL) can display multimedia learning, both audio, visual, video, text and interactive quizzes that can be accessed online. This study aims to determine the effect of Virtual Dry Lab on Handover Compliance with the SBAR Method for Nursing Students.Method: This study used a pre-experimental design with an Intact Group Comparison design among 58 of nursing students (29 of control and intervention groups). The time given for giving VDL to the intervention group and giving lectures to the control group was 100 minutes. This research instrument used an observation sheet that describes the handover stages as many as 16 steps. The data were analyzed using the Man-Whitney non-parametric test.Results: Result showed that p=0.279 so that there was no significant difference between the intervention group and the control group. Meanwhile, mean of intervention group is 82.75 (SD±14.23), mean of control group is 76.93 (SD±18.75).Conclusion: Compared to lecture and discussion method, VDL has no significant different on students’ compliance on using Handover with SBAR. It implies that VDL has the same effect as the lecture learning method for students’ compliance on using SOP Handover with SBAR. Thus, VDL can be used as a substitution method for lecture and discussion.